Increased Fecal Neopterin Parallels Gastrointestinal Symptoms in COVID-19. Issue 1 (12th January 2021) - Grabherr, Felix; Effenberger, Maria; Pedrini, Alisa; Mayr, Lisa; Schwärzler, Julian; Reider, Simon; Enrich, Barbara; Fritsche, Gernot; Wildner, Sophie; Bellmann-Weiler, Rosa; Weiss, Günter; Scholl-Bürgi, Sabine; et al.
Abstract : INTRODUCTION: Coronavirus disease (COVID-19) has spread from Wuhan, China, and become a worldwide pandemic. Most patients display respiratory symptoms but up to 50% report gastrointestinal symptoms. Neopterin is a surrogate marker for viral inflammation, and its production by macrophages is driven by interferon-γ. METHODS: We measured fecal neopterin in 37 hospitalized COVID-19 patients not requiring intensive care measures and 22 healthy controls. RESULTS: Fecal neopterin was elevated in stool samples from COVID-19 patients compared with that in samples from healthy controls. Especially, patients reporting gastrointestinal symptoms exhibited increased fecal neopterin values. DISCUSSION: COVID-19 is associated with an inflammatory immune response in the gastrointestinal tract.